New insights on the effect of the hydrolysing agents in the synthesis of pristine fibrous silica zeolite X for enhancement of side chain methylation of toluene: Theoretical and experimental studies. (1st May 2022) - Aziz, M.A.H.; Jalil, A.A.; Hussain, I.; Izan, S.M.; Setu, S.A.; Matmin, J.
Graphical abstract: Highlights: DFT effectively discovered the nature of structure of hydrolysing agents. Hydrolysing agent play a vital role in formation of EFAl species. The denser of dendrimeric silica fibers retarded the coke formation. Thermodynamic revealed Boudouard reaction was the main source of coke formation. FZXN showed superior performance with 49.6 % yield styrene and ethylbenzene. Abstract: This article aims to clarify the role of hydrolysing agent in the synthesis of a pristine fibrous silica zeolite X (FZX) catalyst using DFT simulation, thermodynamics, and experimental data. FZX was fabricated using various hydrolysing agents such as urea (FZXU), formamide (FZXF) and N, N methylenediacrylamide (FZXN), to perform the side chain methylation of toluene process. It was found that disparity of hydrolysing agents resulted in different degree of silica hydrolysation which eventually altered the each FZX catalyst properties. Based on the chemical reactivity and visualized charge distributions as revealed by the DFT simulations, it was discovered that most electronegative regions located around negatively charged oxygen in hydrolysing agents structure exhibited a higher degree of silica hydrolysation resulted in excellent catalyst behaviour. Higher density of dendrimeric silica fiber in FZXN reduced the coke formation and induced the formation of extra-framework alumina (EFAl) species. The hydrolysing agents also affect the basicity of the decorated FZX catalyst and followed the sequence FZXN > FZXU > FZXF. The FZXN exhibited higher side chain methylation of toluene catalytic activity of 57 % toluene conversion and 49.6 % of styrene and ethylbenzene yield. Furthermore, a thermodynamic analysis was carried out, and it was discovered that the Boudouard reaction was the primary source of carbon deposition during the side chain methylation of toluene.